MicroRNA-Mediated Gene Silencing in Plant Defense and Viral Counter-Defense - Liu, Sheng-Rui; Zhou, Jing-Jing; Hu, Chun-Gen; Wei, Chao-Ling; Zhang, Jin-Zhi (Frontiers in Microbiology, 2017)
MicroRNAs (miRNAs) are non-coding RNAs of approximately 20-24 nucleotides in length that serve as central regulators of eukaryotic gene expression by targeting mRNAs for cleavage or translational repression. In plants, miRNAs are associated with numerous regulatory pathways in growth and development processes, and defensive responses in plant–pathogen interactions. Recently, significant progress has been made in understanding miRNA-mediated gene silencing and how viruses counter this defense mechanism. Here, we summarize the current knowledge and recent advances in understanding the roles of miRNAs involved in the plant defense against viruses and viral counter-defense. We also document the application of miRNAs in plant antiviral defense. This review discusses the current understanding of the mechanisms of miRNA-mediated gene silencing and provides insights on the never-ending arms race between plants and viruses.